Educational innovations in preparing practical psychologists on the basis of competence - Lozova Olga (Borys Grinchenko Kyiv Metropolitan University, 2016)
The article examines the dynamics of changes in higher education of psychologists in the United States from the the 1970s to the present time. The necessity to update the content of professional training of psychologists is presented in the context of the prospects of Ukraine's membership in the European Union. This update should be done not by blindly copying foreign educational programs, but via adapting the experience of other countries with the best traditions of national higher education. The experience of strategic development and implementation of requirements of the European standard (EuroPsy) and the «Harmonisation of European Educational Structures» project in educational programs of Borys Grinchenko Kyiv University is presented. The upgrade of educational programs is described in the context of unification with European standards for future psychologists training. The competences of practical psychologists were made consistent with EuroPsy mode regarding (a) functions of psychologist and (b) competencies psychologist. Meanwhile, general competences of psychologists were made consistent with the Tuning project (c), professional and cognitive (d) and professional practice (e) competences were developed by the Applied Psychology Department of Borys Grinchenko Kyiv University. All competences of psychologists (a total of 14) were divided into basic (6) and auxiliary (8) groups. Programmatic innovations designed to provide qualifications and competitiveness to bachelors and masters were described. Programs consist of modules which include: compulsory subjects aimed at creating general and professional competences, optional subjects, different practices and the final student examination.